Nuclear Weapons: Who’s in Charge? - Miall, Hugh. author. aut Link
XI, 167 p.
Keywords: Ever since the possibility of nuclear fission arose in the minds of the physicists of the 1930s, nuclear weapons seem to have had a momentum of their own. In charge of them, and driven by them, are the nuclear decision-makers. This book takes the reader behind the tests and deployments of bombs and missiles to reveal who takes the decisions to develop nuclear weapons and what kind of people they are. Ranging from the laboratories where 'Star Wars' weapons are being invented, to the Design Bureau where Soviet missiles are developed, to Mururoa Atoll, testing site of the French neutron bomb, to the lake-side compound in the Beijing, from which the modernisation of Chinese nuclear weapons is directed, to the Atomic Weapons Research Establishment at Aldermaston, where warheads for British nuclear weapons are designed, the author asks: who is in charge of nuclear weapons?